EFFECT OF WOODFUEL CONSUMPTION ON UNDER FIVE AND INFANT MORTALITY IN SUB SAHARAN AFRICAN COUNTRIES: SYSTEM GMM APPROACH - YAKUBU, YAHAYA; HABU, SHEHU (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
This study aims to investigate the effect of woodfuel consumption on under-five and infant mortality in Sub-Saharan African countries by using a panel data set of 44 Sub-Saharan African countries spanning from 2011 to 2019. System Generalized Method of Moments (GMM) was used in analyzing the data. The estimated GMM result revealed that woodfuel consumption is positively associated with both under-five and infant mortality. This implies that a 1% increase in woodfuel consumption increases under-five and infant mortality by .0000579% and .0000304%, respectively. The study further reveals that per capita income, government health expenditure, and food availability were significant determinants of under-five and infant mortality in Sub-Saharan African countries. The findings of this study revealed concern for population health and the future of the labor force in the region. The study recommends that Sub-Saharan African governments, non-governmental organizations, donor agencies, and foundations make clean cooking energy, such as electricity, gas, and solar, available and affordable to households; this would facilitate the transition from wood fuel to cleaner fuel.